Radiation spectroscopy of irradiated VVER-1200 fuel with burnable Am-absorber: A computational approach; Applied Radiation and Isotopes; Vol. 218 - Bedenko S. V. Sergey Vladimirovich; Vlaskin G. N. Gennadiy Nikolaevich; Polozkov S. D. Sergey Dmitrievich; Veretennikov D. G. Dmitry Gennadjevich; Demin A. S. Aleksey Sergeevich; Ghal-Eh N. Nima; Rahmani F. Faezeh (2025, 2025)
Title screen